15-Deoxy-Δ12, 14-prostaglandin J2 up-regulates the expression of 15-hydroxyprostaglandin dehydrogenase through DNA methyltransferase 1 inactivation. (4th March 2019) - Jang, Hye-Ok; Lee, Ha-Na; Woo, Jeong-Hwa; Lee, Ja-Young; Kim, Areumnuri; Lee, Jin Kyung; Kim, Do-Hee; Surh, Young-Joon; Na, Hye-Kyung
Abstract: 15-Hydroxyprostaglandin dehydrogenase (15-PGDH) is the key enzyme that catalyses the conversion of prostaglandin E2 to a keto metabolite. The expression of 15-PGDH is ubiquitously repressed in various human malignancies. However, the molecular mechanisms underlying down-regulation of 15-PGDH expression remain largely unknown. 15-Deoxy-△ 12, 14 -prostaglandin J2 (15d-PGJ2 ), an endogenous ligand of peroxisome proliferator-activated receptor γ, has been reported to have anti-inflammatory and anticarcinogenic activities. In the present study, we have found that 15d-PGJ2 induces expression and catalytic activity of 15-PGDH in human breast cancer (MDA-MB-231) cells. 15d-PGJ2 decreased the level of CpG methylation in the 15-PGDH promoter in MDA-MB-231 cells as determined by the bisulphite genome sequencing and methyl-specific PCR. 15d-PGJ2 inhibited the catalytic activity of methyltransferase 1 (DNMT1) but did not influence its expression. Biotinylated 15d-PGJ2 directly interacted with DNMT1 and reduced its catalytic activity. Chromatin-immunoprecipitation analysis revealed that 15d-PGJ2 significantly attenuated DNMT1 binding to the activator protein-1 transcription factor present in the 15-PGDH promoter region. A nonelectrophilic analogue 9, 10-dihydro-15d-PGJ2 failed to suppress the methylation of CpG islands present in 15-PGDH promoter and did not affect both DNMT1 activity and 15-PGDH expression. These findings suggest that the α, β-unsaturated carbonyl group present in 15d-PGJ2 is essential for its inactivation on DNMT1 and expression of 15-PGDH. In conclusion, 15d-PGJ2 plays as a hypomethylating agent through direct interaction with DNMT1 and consequently suppresses DNMT1-mediated hypermethylation of 15-PGDH promoter, leading to up-regulation of 15-PGDH expression.